(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The goal of this research is to synthesize novel Schiff base-derived quinazolinone derivatives (4a and 4b) with improved antibacterial activities. Chemical procedures and spectrophotometric (IR and NMR) techniques were used to study and describe the produced compounds. Antibacterial screening tests for the target compounds were implemented against two gram-positive strains (Staphylococcus aureus, Staphylococcus faecalis) and two gram-negative strains (Escherichia coli, salmonella typhi) by scaling the diameter of the zone of bacterial inhibition. The results of these tests indicate that the synthesized Schiff bases exhibit an accepted level of biological activity against these microorganisms.